Jewish Traditions in Latin American Context ‒ The Creation of an Intercultural Diaspora in Argentina: from the Notion of “Melting Pot” to Contemporary Identity Politics - Fischman, Fernando Damián (2021)
This article explores sociocultural and political changes in Argentina that allowed for the passage from the practice of Jewish rituals in private to the display of traditional expressive forms in public. Focusing on personal narratives from children of Jewish immigrants to Argentina about their childhood experiences in the 1930s and 40s and on festival celebrations performed currently in the streets of Buenos Aires, I analyze the implications of the contextualization of traditional practices, originally performed within the collective?s boundaries to their open exhibition to society at large.I begin by presenting some of the narratives about the WWII pre war and war period in Argentina that I collected in the 1990s. Then, I examine street performance events that began to be staged at the same time by Jewish organizations in conjunction with celebrations derived from the identity politics that started to be in place in those years. I thus contrast the narratives about the public expression of Jewish identity in the first half of the XXth century with the contemporary discursive expressions through which Jewish culture is explicitly put on display. The concept of ?performance? provides the analytical framework, and the analysis focuses on the social and political implications of such staging for the shaping of new expressive forms related both to a precedent diasporic Jewish culture and to the intercultural dialogues accomplished in contemporary Argentine society.